The creation of a learning system for the teachers from higher medical school as a perspective aim (according to the expert group meeting reports of the international research project “Tempus IV”) - S. I. Zmeev (Сеченовский вестник)
This article deals with the problems of increasing professional competence of teachers of medical school.